Estimation of landfill gas generation in a municipal solid waste disposal site by LandGEM mathematical model - S.S. Hosseini; K. Yaghmaeian; N. Yousefi; A.H. Mahvi (Global Journal of Environmental Science and Management)
Anaerobic decomposition of organic compounds in landfills is responsible for generation of greenhouse gases. The present study aimed to determine the total gas and methane emission from a landfill located in Hamedan (west of Iran) from 2011 to 2030. LandGEM 3.02 model was used to estimate the gas emission with the volumetric methane percent of 60%, production potential of 107, and methane generation rate of 0.2. Spatial distribution of annual methane and total landfill gas emission rate in the study area at three decades were provided through ArcGIS software. The results showed that organic and food wastes had the maximum amounts in the solid waste stream (over 75%). The results showed that 4.371×108 m3 methane would be produced after 20 years, mostly (4.053×106m3) in the first year. In addition, methane production capacity in Hamedan landfill site was 107 m3/Mg. According to the results, the maximum and minimum gas generation rates are in summer (the hottest season) and winter (the coldest season) respectively. The results of the LandGEM model represented that the total gas and methane generation rates will be significant in the first 10 years. The potential of rapidly degradable organic compounds for gas emission will be higher than that of slowly degradable organic compounds. The results obtained in the present study can be beneficially used in planning for energy production and other applications in landfill sites.